1985
DOI: 10.1016/s0022-5347(17)47281-8
|View full text |Cite
|
Sign up to set email alerts
|

Nonchromaffin Paraganglioma of the Retroperitoneum

Abstract: We reviewed 37 cases described previously in the literature to provide a patient operated upon for a retroperitoneal nonchromaffin paraganglioma with qualified advice concerning followup examinations and prognosis. This type of tumor apparently grows slowly and metastasizes late. A radical operation is the treatment of choice and provides a good prognosis. We suggested that our patient undergo clinical followup and ultrasound investigations at 3 to 6-month intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…[6][7][8] In a review by Fries and Chamberlin, 85% of 205 EAPs were intraabdominal (retroperitoneum), 12% intrathoracic and 3% in the neck. 9 A broad range of cytologic features has been described in the literature for EAP, [10][11][12][13][14][15][16][17][18] but the majority of the tumors possess a hemorrhagic background, moderately sized tumor cells with delicate cytoplasm and round to oval nuclei with a tendency toward anisokaryosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In a review by Fries and Chamberlin, 85% of 205 EAPs were intraabdominal (retroperitoneum), 12% intrathoracic and 3% in the neck. 9 A broad range of cytologic features has been described in the literature for EAP, [10][11][12][13][14][15][16][17][18] but the majority of the tumors possess a hemorrhagic background, moderately sized tumor cells with delicate cytoplasm and round to oval nuclei with a tendency toward anisokaryosis.…”
Section: Discussionmentioning
confidence: 99%
“…Krugger-Baggesen et al 1 reported that of 15 patients who had undergone a radical operation, none had died of the disease, although one patient had recurrent disease 7 years later. Among the 15 patients who had undergone incomplete excision, 6 had died of recurrent tumour but in each case local invasion had been apparent at laparotomy; the other 9 were alive with recurrent disease several years after the excision.…”
Section: Discussionmentioning
confidence: 99%
“…The extraadrenal paraganglia are divided anatomically into three groups: (1) the branchiomeric paraganglia are chemoreceptors associated with the blood vessels and cranial nerves of the head and neck, (2) the intravagal paraganglia located in the perineurium of the vagus nerve, and (3) the aorticosympathetic paraganglia located along the sympathetic chain in the retroperitoneum [2]. Extraadrenal retroperitoneal paragangliomas affect males and females equally, and the average age at presentation is between 37 and 42 years [3][4][5]. In one study, 8 of 22 patients with extraadrenal paraganglioma presented with functional tumors [3].…”
Section: Discussionmentioning
confidence: 99%